"Gender-based Violence (GBV) and HIV, they are like sister and brother": barriers and facilitators to GBV screening and referral in public HIV treatment settings in Uganda - Dorothy Thomas; Alisaati Nalumansi; Mira Reichman; Mine Metitiri; Brenda Kamusiime; Vicent Kasiita; Grace K Nalukwago; Joseph Kibuuka; Lylianne Nakabugo; Florence Nambi; Timothy Muwonge; Jane Simoni; et al. (BMC, 2023)
Abstract Background People living with HIV are vulnerable to gender-based violence (GBV), which can negatively impact HIV treatment outcomes. National guidelines in Uganda recommend GBV screening alongside HIV treatment services. We explored barriers and facilitators to providers implementing GBV screening and referral in public antiretroviral therapy (ART) clinics in Uganda. Methods We conducted qualitative in-depth interviews. Providers were purposively sampled from 12 ART clinics to represent variation in clinical specialty and gender. We used the Theoretical Domains Framework to structure our deductive analysis. Results We conducted 30 in-depth interviews with providers implementing GBV screening and/or referral. Respondents had a median age of 36 (IQR: 30, 43) years and had been offering post-GBV care to clients for a median duration of 5 (4, 7) years. 67% of respondents identified as female and 57% were counselors. Facilitators of GBV screening and referral included providers having access to post-GBV standard operating procedures and screening tools, trainings offered by the Ministry of Health, facility-sponsored continuing medical education units and support from colleagues. Respondents indicated that referrals were uncommon, citing the following barriers: negative expectations regarding the quality and quantity of referral services; lack of financial resources to support clients, facilities, and referral partners throughout the referral process; and sociocultural factors that threatened client willingness to pursue post-GBV support services. Conclusions Findings from this evaluation support the refinement of GBV screening and referral implementation strategies that leverage facilitators and address barriers to better support individuals living with HIV and who may have heightened vulnerability to GBV.